A three-arm randomized controlled trial protocol: Effects of telephone-based, layperson-delivered wisdom-enhancement narrative therapy and empathy-focused interventions on loneliness, social, and mental health in older adults - Vivien Foong Yee Tang; Da Jiang; Maninder Kahlon; Esther Oi-wah Chow; Dannii Yuen-lan Yeung; Rhonda Aubrey; Kee-Lee Chou (Contemporary Clinical Trials Communications)
Background: Loneliness is an increasingly widespread issue among older adults globally, with significant implications on physical, social, and mental health. While various interventions exist to address this challenge, their long-term effects remain unclear. Using a 3-arm randomized controlled trial, this study aims to evaluate the efficacy of a telephone-based and layperson-delivered wisdom-enhancement narrative therapy (Tele-NT) and empathy-focused program (Tele-EP) against an active control group (ACG) in reducing loneliness. Methods: 282 community-dwelling lonely older adults will be recruited and randomly allocated into 1 of the 3 interventions. Older adults will receive two 30-min intervention per week, over the course of 4 weeks, delivered over the phone by a layperson. Assessments will be conducted in-person at baseline (T0), 1-month (T1), 6-month (T2), and 12-month (T3) post-intervention. The primary outcome will be assessed using the Chinese validated 6-item De Jong Gierveld Loneliness Scale and the Revised UCLA Loneliness Scale. The secondary outcomes will include sleep quality, perceived social support, and depressive symptoms. Potential mediators and moderators will also be explored. The data will be analysed using linear mixed models on an intention-to-treat basis. Discussion: This RCT is effective, Tele-NT and/or Tele-EP could serve as a model for broader implementation in the community, offering practical solutions to mitigate loneliness and its associated health burdens in the aging populations. Trial registration: This trial is registered with the Chinese Clinical Trial Registry; ChiCTR2300070179 on April 4, 2024.